Экватор - наш! - Тамоников Александр Александрович (Роман о российском спецназе, 2018)
Экземпляры: ф.7 (20180906) / Инвентарный номер: 50412 / Цена: 291.00 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Т 17 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6-44